Investigating the reliability of machine learning algorithms as a sustainable tool for total suspended solid prediction - Sami B.H.Z.; Jee khai W.; Sami B.F.Z.; Ming Fai C.; Essam Y.; Ahmed A.N.; El-Shafie A. (Ain Shams University, 2023)
Forecasting; Iron; Learning algorithms; Machine learning; Mean square error; Neural networks; Potable water; Reservoirs (water); Turbidity; Water quality; Water supply; Coefficient of determination; Iron concentrations; Output parameters; Performance criterion; Root mean square errors; Strong correlation; Total suspended solids; TSS concentration; Predictive analytics